2014
DOI: 10.1002/2013jc009220
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Barents Sea winter air‐sea exchanges on Fram Strait dense water transport

Abstract: Impacts of extreme Barents Sea air-sea exchanges are examined using the HadCM3 coupled ocean-atmosphere model. Variability in the Barents Sea winter air-sea density flux is found to be a potentially significant factor in determining changes in the southward transport of dense water through Fram Strait. The density flux variability is primarily driven by the thermal term, F T , due to heat loss to the atmosphere. The other two terms (haline flux and ice formation) play a relatively minor role. The difference in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…As the stationary PF, rather than the mobile sea ice edge, has become the limiting factor controlling the northern boundary of the surface area available for AW cooling in winter, the buffering effect to BSW temperature from the variations of sea ice conditions has decreased. Observations show a change in BSW properties over the same time period resulting in denser BSW, which could in turn result in a deeper settling depth of BSW once exported to the Arctic Basin through St. Anna Trough (Dmitrenko et al 2015), with potential far-reaching impacts for the dense water outflow through Fram Strait (Lique et al 2010;Moat et al 2014) or the density of the Denmark Strait overflow (Karcher et al 2011), both of which are important for the deeper branch of the AMOC. analysis of SST (green box), the region used for Hovmoller analysis (blue-dashed box), the cross-front transect (light-blue line), the area selected for calculating the contribution of sea ice to AW/BSW (dark-blue box), the area selected for 100 -300 m BSW properties from EN4 data and 0 -100 m ArW properties from EN4 data (cyan-dashed box), the area selected for 0 -100 m surface BSW properties from EN4 data south of the PF (yellow-dashed line), the the Kola section (orange line) and the Fugløya-Bear Island section (red line).…”
Section: Discussionmentioning
confidence: 99%
“…As the stationary PF, rather than the mobile sea ice edge, has become the limiting factor controlling the northern boundary of the surface area available for AW cooling in winter, the buffering effect to BSW temperature from the variations of sea ice conditions has decreased. Observations show a change in BSW properties over the same time period resulting in denser BSW, which could in turn result in a deeper settling depth of BSW once exported to the Arctic Basin through St. Anna Trough (Dmitrenko et al 2015), with potential far-reaching impacts for the dense water outflow through Fram Strait (Lique et al 2010;Moat et al 2014) or the density of the Denmark Strait overflow (Karcher et al 2011), both of which are important for the deeper branch of the AMOC. analysis of SST (green box), the region used for Hovmoller analysis (blue-dashed box), the cross-front transect (light-blue line), the area selected for calculating the contribution of sea ice to AW/BSW (dark-blue box), the area selected for 100 -300 m BSW properties from EN4 data and 0 -100 m ArW properties from EN4 data (cyan-dashed box), the area selected for 0 -100 m surface BSW properties from EN4 data south of the PF (yellow-dashed line), the the Kola section (orange line) and the Fugløya-Bear Island section (red line).…”
Section: Discussionmentioning
confidence: 99%
“…These overflows are fed by waters of Arctic and Atlantic origin that have been transformed in the Nordic seas by interior mixing and by exchanges with the atmosphere. Regarding the Arctic watermass transformations, the Nordic seas play a preconditioning role by cooling the warm Atlantic waters before they enter the Arctic Ocean through Fram Strait and the Barents Sea (Moat et al 2014). The heat transport of these Atlantic waters has a strong impact on Arctic basin properties (Polyakov et al 2017;Barton et al 2018) and Arctic climate (Docquier et al 2019), and it has been demonstrated to be a source of predictability on interannual to decadal time scales in the Nordic seas and Barents Sea in CMIP5 models (Langehaug et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…(2010) and Moat et al. (2014) have shown that variability in BSW density impacts the density of AIW exiting the Arctic Basin through Fram Strait, a contributor to the deeper branch of the Atlantic meridional overturning circulation (AMOC).…”
Section: Introductionmentioning
confidence: 99%
“…The transition from BSW to the distinctly different salinity-stratified ArW present in the northern Barents Sea is marked by the Polar Front at ∼76.5°N (Barton et al, 2018;Loeng, 1991;Oziel et al, 2016). Lique et al (2010) and Moat et al (2014) have shown that variability in BSW density impacts the density of AIW exiting the Arctic Basin through Fram Strait, a contributor to the deeper branch of the Atlantic meridional overturning circulation (AMOC).…”
Section: Introductionmentioning
confidence: 99%